Acetabular volume and femoral coverage change following Dega-like osteotomy in treatment of developmental dysplasia of the hip. Issue 3 (19th July 2021) - Gigi, Roy; Lawniczak, Dominik; Kurian, Binu; Madan, Sanjeev; Fernandes, James
Abstract : Although Dega's acetabuloplasty has become a commonly used osteotomy, there is still an ongoing debate regarding its impact on the volume and depth of the acetabulum. The purpose of our study was to assess the postoperative images of the transverse acetabular plane and version obtained from developmental dysplasia of the hip (DDH) patients after a modified Dega osteotomy. We performed a retrospective study of the morphologic indices obtained from the pelvic X-rays and computer tomography (CT) scans of patients with DDH, who were operated in our institution between July 2005 and October 2013, using the modified Dega osteotomy. Preoperative and postoperative pelvic X-rays were used to measure the acetabular index and the acetabular (ACM) angle. The postoperative CT scans were used to measure the acetabular anteversion angle (AAA), acetabular depth and depth of acetabular coverage [total acetabular index (TAI)]. The contralateral unaffected hips served as control. The postoperative acetabular indices and ACMs showed a significant improvement, with near-normal values measured 1 year after the surgery. Comparing the CT scan parameters (AAA, TAI and the depth of acetabulum) showed that TAI and the depth of acetabulum were not significantly different between the groups (TAI: P = 0.423; depth of acetabulum: P = 0.132), whereas AAA comparison implied a slight advantage of the DDH hips (17.6° DDH vs. 13.3° contralateral, P = 0.001). On the basis of images set of acetabular morphometric parameters, our study substantiates previous reports on an increase of acetabular volume and a significant improvement of femoral head coverage for patients with DDH who underwent Dega acetabuloplasty. Level of evidence: Level III – retrospective comparative study.